2007
DOI: 10.1666/06-121.1
|View full text |Cite
|
Sign up to set email alerts
|

The Pennsylvanian (Moscovian) Izvarino Section, Donets Basin, Ukraine: A Multidisciplinary Study on Microfacies, Biostratigraphy (Conodonts, Foraminifers, and Ostracodes), and Paleoecology

Abstract: The mid-Moscovian Izvarino section, Donets Basin, eastern Ukraine, exhibits a complete sedimentological record of siliciclastics (sandstones, siltstones, and calcareous shales) with limestone intercalations and, rarely, coal seams. A multidisciplinary study including microfacies analysis, systematic paleontology (conodonts, fusulinoideans, and ostracodes), biostratigraphy, and paleoecology was focused on the limestones, from limestone L4 through limestone M1, and the adjacent marine shales. Based on sedimentol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 60 publications
0
17
0
1
Order By: Relevance
“…The new radiometric ages obtained in our study require significant revisions to the absolute age calibration of the global Carboniferous time scale. Our new ages meet the necessary prerequisites for global time scale calibration: all radiometric samples were collected and documented within the well‐established local lithostratigraphic framework of the Donets Basin [ Aisenverg et al , 1963, 1975], and the collected samples are therefore precisely constrained within the exceptionally complete biostratigraphic framework of the basin [ Aizenverg et al , 1979; Davydov , 1992; Davydov et al , 2008; Fohrer et al , 2007; Nemyrovska et al , 1999; Poletaev et al , 1991]. As we have emphasized in our description of the Donets Basin succession, its multitaxa biostratigraphy may be straightforwardly correlated with the Tournaisian and Visean type sections in western Europe, and the Serpukhovian, Bashkirian, Moscovian, Kasimovian, Gzhelian and Asselian type sections in the Moscow Basin and Urals (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The new radiometric ages obtained in our study require significant revisions to the absolute age calibration of the global Carboniferous time scale. Our new ages meet the necessary prerequisites for global time scale calibration: all radiometric samples were collected and documented within the well‐established local lithostratigraphic framework of the Donets Basin [ Aisenverg et al , 1963, 1975], and the collected samples are therefore precisely constrained within the exceptionally complete biostratigraphic framework of the basin [ Aizenverg et al , 1979; Davydov , 1992; Davydov et al , 2008; Fohrer et al , 2007; Nemyrovska et al , 1999; Poletaev et al , 1991]. As we have emphasized in our description of the Donets Basin succession, its multitaxa biostratigraphy may be straightforwardly correlated with the Tournaisian and Visean type sections in western Europe, and the Serpukhovian, Bashkirian, Moscovian, Kasimovian, Gzhelian and Asselian type sections in the Moscow Basin and Urals (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Conodonts are locally abundant in the Carboniferous of the Donets Basin, but have been studied only since the late 1970s [ Kozitskaya et al , 1978]. Study has focused in the Bashkirian, Moscovian and lower Kasimovian portions of the successions [ Fohrer et al , 2007; Nemyrovska , 1999; Nemyrovska et al , 1999]. Conodonts provide reasonable correlation in the Mississippian and Late Pennsylvanian, and an excellent zonation and correlation for early Middle Pennsylvanian (Figure 2), although they are quite provincial in the middle Moscovian [ Goreva and Alekseev , 2007].…”
Section: Geologic and Stratigraphic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing fusulinid distribution data was integrated with the results of this study (Brazhnikova, 1939a(Brazhnikova, , 1939b(Brazhnikova, , 1951Putrja, 1940Putrja, , 1956Manukalova, 1950aManukalova, , 1950bPogrebnyak, 1975;Ueno in Fohrer et al, 2007;Davydov and Khodjanyazova, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…The lower part of the "N" formation from limestone N 1 to the N 4 or N 5 limestone was correlated with Myachkovian strata in the Moscow Basin. Subsequent research (Solovieva, 1986;Vachard and Maslo in Izart et al, 1996;Ueno in Fohrer et al, 2007) accepted the biozonation proposed by Kireeva (1951). A recent detailed biostratigraphic study (Khodjanyazova et al, 2011, Khodjanyazova et al, 2012 revealed an inconsistency in the generally accepted Donets biostratigraphy and proposed a new biostratigraphic zonation ( Fig.…”
Section: Fusulinid Biostratigraphymentioning
confidence: 97%